(3GdYfa VO GdeQCI hGdMeGjI GdebQQI dehGLgJg ai GdTQjYI GdESdGejI (B/ s - (3YHdI YHOGdYRjR YGeQs; (3YHOGdYRjR QeVGf Secs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhd gPG GdHMK deMI YGeI Yf eaghe GdYfa hOhGaYg hBKGQg heaghe GdYfa VO GdeQCI hBKGQg Ydi GdeQCI hGdWad hGdeLJeY hbO NUU GdbSe GdChd ddYfa GdPj jeGQS VO GdeQCI ai GdeMjW GdCSQi hGMJhi NJGf GdEfGK hLQGFe GdEjPGA GdHOfj VO GdeQCI ef JLGhR Mb GdJCOjH GdELgGV hgLQ GdYGFdI GdeGOj hGdeYfhj CeG GdbSe GdKGfi aJfGhd UhQB ef GdYfa GdELJeGYi VO GdeQCI hbO bSe gPG GdbSe Edi LQGFe MOjI hLQGFe ZjQ MOjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdGSdGejI, (B2009s
(3HHdjhLQGajG(B: (3UaMGJ (B546-566s
Keywords: (3GdTQjYI GdESdGejIs; (3GdMeGjI GdebQQI dehGLgI GdYfas; (3GdMbhb GdbGfhfjI ddeQCI s; (3GdYfa VO GdeQCIs; (3NJGf GdGfGKs; (3GdEjPGA GdHOfj hGdfaSjs; (3GdEHGMIs; (3GdELgGVs; (3gLQ GdYGFdIs; (3GdHZGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs